2008
DOI: 10.1038/jp.2008.21
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac troponin T and N-terminal-pro-B type natriuretic peptide reflect myocardial function in preterm infants

Abstract: Background: Cardiovascular compromise is increasingly recognized in preterm infants. Currently, echocardiography is the best tool to assess myocardial contractility and guide management. Elevated levels of cardiac troponin T (cTnT) and N-terminal-pro-B type natriuretic peptide (NTpBNP) are associated with poor myocardial contractility and low cardiac output in adults.Objective: To examine the range of cTnT and NTpBNP in preterm infants, to correlate NTpBNP and cTnT with echocardiographic markers of cardiac fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 21 publications
1
33
1
5
Order By: Relevance
“…BNP has therefore been established as an accurate indicator of cardiovascular disease in infants and children [17]. BNP levels are closely related to myocardial dysfunction as diagnosed by echocardiography [18,19]. We found BNP levels to correlate with echocardiographic parameters representing ventricular size and volume.…”
Section: Discussionmentioning
confidence: 58%
“…BNP has therefore been established as an accurate indicator of cardiovascular disease in infants and children [17]. BNP levels are closely related to myocardial dysfunction as diagnosed by echocardiography [18,19]. We found BNP levels to correlate with echocardiographic parameters representing ventricular size and volume.…”
Section: Discussionmentioning
confidence: 58%
“…The previous study 35 has also shown that NT-proBNP on day 3 significantly correlated with LA/Ao ratio, PDA diameter and descending aorta end-diastolic velocity, whereas the other study 37 reported that NT-proBNP at 12 h of age significantly correlated with respiratory distress syndrome and LA:Ao ratio, but not with ductal diameter and a negative correlation was seen between NT-proBNP and left ventricular mean velocity of circumferencetial fiber shortening and shortening fraction. The conflicting results in the degree of correlation between plasma level and related variables may reflect the differences in the postnatal age at time of measurement.…”
Section: Discussionmentioning
confidence: 87%
“…However, while the place of echocardiography in neonates is firmly established in the detection of left ventricular myocardial dysfunction [31,32], it demands a high degree of technical competence and skilled interpretation. El-Khuffash [33] has suggested that plasma cardiac troponin (cTnT) should be used as an indirect marker of myocardial contractility and degree of myocardial compromise in preterm infants when specialized echocardiography is not readily available. Subsequent confirmatory studies of the usefulness of this method are lacking however.…”
Section: Inotropymentioning
confidence: 99%